Root activities and arsenic translocation of Avicennia marina (Forsk.) Vierh seedlings influenced by sulfur and iron amendments. (October 2018) - Lin, Yushan; Fan, Jin; Yu, Jinfeng; Jiang, Shan; Yan, Chongling; Liu, Jingchun
Abstract: Sulfur and iron are abundant and have close, complex interactions with the biogeochemical cycle of arsenic (As) in mangrove ecosystems. A hydroponic experiment was conducted to investigate the influences of variable SO4 2− and Fe 2+ supplies on radial oxygen loss (ROL), iron plaque formation and As translocation in Avicennia marina upon exposure to As(III). The results indicate that A. marina is an As-tolerant plant, the application of iron and sulfur not only showed positive growth effects but also induced much higher amounts of ROL-induced iron plaque formation on root surfaces. The presence of iron plaque remarkably improved the proportion of As sequestration near this area but consequently reduced the proportion of As translocation in root. Therefore, it is concluded that iron plaque may act as a barrier for protection against As, and iron and sulfur play important roles in controlling the growth and translocation of As in A. marina seedlings. Highlights: Avicennia marina exhibit a high As tolerance potential. The supplies of iron and sulfur showed positive growth effects under As stress. Both iron and sulfur facilitated the formation of ROL-induced iron plaque. The presence of iron plaque may act as a barrier for protection against As.